2021
DOI: 10.1111/and.14005
|View full text |Cite
|
Sign up to set email alerts
|

Oyster peptide prevents the occurrence of exercise‐hypogonadal male condition by improving the function of pituitary gonadal axis in male rats

Abstract: This study evaluates the protective role of oyster peptide (OP) on the occurrence of Exercise‐Hypogonadal Male Condition. Male rats were given heavy‐load swimming training and / or OP was supplemented for 6 consecutive weeks. After heavy‐load training, sperm count, sperm viability and sperm motility in epididymis, testosterone in serum and testis, glutathione peroxidase (GSH‐px) and androgen receptor (AR) in testis and mating times were remarkably decreased, malondialdehyde (MDA), capture latency and mating la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Compared with source proteins, peptides have significantly higher bioavailability due to their relatively low molecular weights (Wang & Selomulya, 2020), making them beneficial to the elderly, pregnant women, and athletes with special nutritional needs. A large number of studies have shown that oyster peptides obtained from oyster meat through enzymatic hydrolysis and refinement have anti‐cancer properties (Umayaparvathi et al ., 2014) can improve cognitive impairment via restoring glial cell dysfunction and neuronal injury (Zhu et al ., 2021), enhance antioxidant and aphrodisiac activities (Zhang et al ., 2019), and they also have anti‐wrinkle recovery photo‐aging properties (Bang et al ., 2020), anti‐oxidation properties (Wang et al ., 2014), and other biological activities (Jin et al ., 2021). Therefore, extensive and in‐depth research into various biologically active functions of oyster peptides supports the development and application of oyster peptides as marine functional food ingredients in the fields of nutrition and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with source proteins, peptides have significantly higher bioavailability due to their relatively low molecular weights (Wang & Selomulya, 2020), making them beneficial to the elderly, pregnant women, and athletes with special nutritional needs. A large number of studies have shown that oyster peptides obtained from oyster meat through enzymatic hydrolysis and refinement have anti‐cancer properties (Umayaparvathi et al ., 2014) can improve cognitive impairment via restoring glial cell dysfunction and neuronal injury (Zhu et al ., 2021), enhance antioxidant and aphrodisiac activities (Zhang et al ., 2019), and they also have anti‐wrinkle recovery photo‐aging properties (Bang et al ., 2020), anti‐oxidation properties (Wang et al ., 2014), and other biological activities (Jin et al ., 2021). Therefore, extensive and in‐depth research into various biologically active functions of oyster peptides supports the development and application of oyster peptides as marine functional food ingredients in the fields of nutrition and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…Oyster peptide supplement could significantly support the function of the hypothalamus-pituitary gonad axis in male rates during heavy load training. This supplement can considerably reduce OS in testis by up-regulating steroidogenic enzyme expression to promote steroidogenesis and spermatogenesis (Jin et al, 2021b). In another study, oyster peptides and oyster powder were used to feed rats with reproductive dysfunction induced by cyclophosphamide.…”
Section: Protecting Effects and Antioxidant Activitiesmentioning
confidence: 99%